2021
DOI: 10.3892/etm.2021.10276
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated LINC00319 aggravates neuronal injury induced by oxygen‑glucose deprivation via modulating miR‑200a‑3p

Abstract: Ischemic stroke is one of the main causes of physical disability and mortality worldwide. Long non-coding RNAs (lncRNAs) are reported to be dysregulated in various biological progressions and serve important roles in pathological processes of cerebral ischemia. However, their biological actions and potential mechanisms in the progression of ischemic stroke remain unknown. The present study aimed to investigate the functions of LINC00319 on ischemic brain injury. It was identified that LINC00319 was significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…There is increasing evidence that miRNAs, such as miR-125a-5p, miR-125b-5p, and miR-143-3p, play important roles in the process of stroke ( 14 ). Further, research has shown that miR-200a-3p plays a critical role in ischemic stroke modulated by long non-coding RNAs ( 15 ); however, it is unclear whether miR-200a-3 interacts with circsRNAs to affect the process of stroke.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence that miRNAs, such as miR-125a-5p, miR-125b-5p, and miR-143-3p, play important roles in the process of stroke ( 14 ). Further, research has shown that miR-200a-3p plays a critical role in ischemic stroke modulated by long non-coding RNAs ( 15 ); however, it is unclear whether miR-200a-3 interacts with circsRNAs to affect the process of stroke.…”
Section: Introductionmentioning
confidence: 99%